2021
DOI: 10.1094/pdis-06-20-1401-re
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Plant-Derived Essential Oils on Pathogens of Pulse Crops

Abstract: Pulse crops such as chickpeas, lentils, and dry peas are grown widely for human and animal consumption. Major yield and quality limiting constraints include diseases caused by fungi and oomycetes. The environmental and health concerns of synthetic fungicides use for disease management, emergence of fungicide-resistant pathogens, and demand for organic pulse crop products necessitate the search for effective alternatives. Safe and environmentally friendly plant-derived essential oils (EOs) have been reported ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 59 publications
2
21
1
Order By: Relevance
“…They are extracted from more than 17,000 aromatic plants belonging to angiosperm families: Lamiaceae, Rutaceae, Myrtaceae, Zingiberaceae and Asteraceae [14], and they have multiple antibacterial, antifungal, antiviral, antiparasitical, insecticidal, medicinal and cosmetic applications [15]. At least 16 different publications [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] presented data on EOs antifungal activities from 35 plants against F. avenaceum (Table 1). All the authors used either agar diffusion methods (paper discs or wells), or an agar dilution method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are extracted from more than 17,000 aromatic plants belonging to angiosperm families: Lamiaceae, Rutaceae, Myrtaceae, Zingiberaceae and Asteraceae [14], and they have multiple antibacterial, antifungal, antiviral, antiparasitical, insecticidal, medicinal and cosmetic applications [15]. At least 16 different publications [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] presented data on EOs antifungal activities from 35 plants against F. avenaceum (Table 1). All the authors used either agar diffusion methods (paper discs or wells), or an agar dilution method.…”
Section: Introductionmentioning
confidence: 99%
“…All the authors used either agar diffusion methods (paper discs or wells), or an agar dilution method. Only one recent paper reported a method for testing the effects of the volatile components [16]. In the application of EOs for controlling the phytopathogens, the bioactivity of volatiles should widely contribute to the fungicidal or fungistatic effect and it is worthy to measure it.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this is the first report of the inhibitory effect of essential oils against A. astaci . Nevertheless, some authors reported a good inhibitory effect of tea tree oil against the mycelial growth of the fish pathogen A. invadans [ 28 ] and of 38 essential oils, including rosemary essential oil and essential oils from some other Lauraceae and Lamiaceae plants, against the mycelial growth of the plant pathogen A. euteiches [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, plants from the Lauraceae and Lamiaceae families, such as Thymbra spicata and Cinnamomum zeylanicum , have been reported to inhibit pathogenic freshwater oomycetes, mostly using the mycelium and zoospores of Saprolegnia spp. as models [ 32 , 34 , 36 , 37 , 38 , 40 ]. In comparison, the inhibitory activity of essential oils and their major components against Aphanomyces spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation